Lessons Learned from the COVID-19 Pandemic in Implant Dentistry Settings - Mohammed Hussein M Hussein Alsharbaty; Moein Hoseini Shirazi; Nawres Bahaa Mohammed; Fatemeh Akbari (Wolters Kluwer Medknow Publications, 2022)
In 2019, Wuhan city of China announced the epidemic of COVID-19 as a public health disaster which has been recognized as an uncommon type of single stranded RNA virus belonging to Coronaviridae family and then quickly spread all over the world. Clinically symptomatic patients are identified as the primary source of COVID-19 transmission. Most of dental procedures require the use of high-speed handpieces which leads to aerosol generation. Implant dentistry is the field of dentistry which deals with prosthetic rehabilitation with minimal aerosol generation ensuring an aseptic surgical environment. There are several decisive recommendations regarding COVID-19 precautions that should be appreciated in implant dentistry. Sharp drills in slow speed drilling machines are preferred during surgery. Regular irrigation with high volume suction is greatly encouraged. Osteotomes are encouraged over ultrasonic devices to minimize the generation of aerosols during surgical procedures. Immediate implants placement is more preferred as the number of visits to the dentists is reduced. Impression techniques should be shifted to the digital approach instead of conventional methods. Full mouth rehabilitation cases requiring complex procedures should be accomplished restrictedly.